Urgensi Pendidikan Anak Usia Dini Dalam Perspektif Hadits di Masa Pandemi Coronavirus - Afifah Fatihakun Ni'mah Wahidah; Muhammad Alfatih Suryadilaga (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
Urgency Parents have an important role for Early Childhood Education especially with the covid outbreak so that children have to learn from home. This article aims to examine the urgency of Early Childhood Education education in the perspective of hadith, especially the hadith on the obligations of parents in educating children, which is associated with conditions in the era of the Coronavirus pandemi. Family is the first and foremost education for a person. Education in the family plays a role in developing character, personality, cultural values, religious and moral values, and simple skills. There is a physical distancing policy so that learning is carried out online (in a network) so that the role of parents is very urgent in ensuring the continuity of their children's education. is the responsibility of the parents; Second, the best gift parents give their children is a good education; Third, parents as the first and foremost madrasa, especially for early childhood, are responsible for their children's education.